Bird Trading at The Pasar Pramuka, Jakarta and the Bird Catching Techniques - Sambas Basuni; Gunawan Setiyani (Media Konservasi, 1989)
The observation of bird trading at the Pasar Pramuka, Jakarta was aimed to know the activity of bud sellers, catchers and consumers. There were 150.000 buds on sale in December 1987, includingthe protected buds. They caught the birds around Klender Jakarta, using the pull-net and the driving techniques. The caught buds were sold to the bird sellers at the Pasar Pramuka. Beside the variety of buds, they also sell everything correlated with bud hunting, like cages, nets, bird food, etc.Usually, the consumers by them for their voice, their appearance, their rareness and for particular aims.